2022
DOI: 10.21037/tlcr-22-555
|View full text |Cite
|
Sign up to set email alerts
|

The improved success rate and reduced complications of a novel localization device vs. hookwire for thoracoscopic resection of small pulmonary nodules: a single-center, open-label, randomized clinical trial

et al.

Abstract: Background: In our previous study, we developed a 4-hook claw-suture localization device for pulmonary nodule resection, which acheived satifisfactory results. Following this, we conducted this single-center, openlabel, randomized clinical trial to compare the success rate and complication rate of this novel localization device and currently widely-used hookwire.Methods: Patients with small pulmonary nodules (0.4-1 cm) who received preoperative localization and thoracoscopic resection at Shanghai Chest Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Fan et al ( 22 ) developed a new disposable lung nodule localization needle (Ningbo SensCure Biotechnology, Ningbo, China), obtaining a localization success rate of 97.8% (133/136) and a localization time of 14.4±6.6 min. Lin et al ( 19 ) reported the localization of SPNs through the injection of methylene blue with a localization time of 7.6±4.8 min for a single nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al ( 22 ) developed a new disposable lung nodule localization needle (Ningbo SensCure Biotechnology, Ningbo, China), obtaining a localization success rate of 97.8% (133/136) and a localization time of 14.4±6.6 min. Lin et al ( 19 ) reported the localization of SPNs through the injection of methylene blue with a localization time of 7.6±4.8 min for a single nodule.…”
Section: Discussionmentioning
confidence: 99%